Nutritional Evaluation of Total Mixed Rations Supplemented with Exogenous Fibrolytic Enzymes and/or Live Yeast Culture in Buffalo Bulls - Reddy, P. Ravikanth; kumar, D. Srinivas; Rao, E. Raghava; Rao, K. Ananda (Indian Journal of Animal Nutrition, 2018)
Four adult buffalo bulls (BW= 377.05Â±43.36 kg) were randomly allotted to four dietary treatments using 4Ã—4 latin square design, The animals in group T1 were fed total mixed ration with roughage: concentrate ratio of 70: 30 while the animals in groups T2, T3 and T4 were fed on the same ration as in T1 but were also supplemented with exogenous fibrolytic enzyme (EFE) @ 15 g/animal/d (T2), live yeast culture @ 10 g/animal/d (T3) and EFE @ 15 g plus live yeast culture @ 10 g/animal/d (T4), respectively. Supplementation of EFE and/or live yeast culture in TMR had no effect on the digestibility of nutrients, fibre fractions and DCP and TDN content of rations. All the buffalo bulls were in positive N, Ca and P balance. The present study indicated that supplementation of either EFE or live yeast culture or both in TMR having roughage: concentrate ratio of 70: 30 had no effect on the nutrient utilization in buffalo bulls.